Elemental analysis in food: An overview - Ibourki, Mohamed; Hallouch, Otmane; Devkota, Krishna; Guillaume, Dominique; Hirich, Abdelaziz; Gharby, Said (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2023)
Due to the risk of occurrence of several food-related diseases, quality control of the human-consumed products is particularly needed. For this purpose, elemental analysis is a useful analytical tool that provides information on the nutritional composition, origin, quality and safety of foods. Currently, existing multielement techniques can be improved with more sensitive detectors and miniaturized solutions. Not to be overlooked, the numerous techniques being developed make sample preparation quicker and easier and allow the analysis of various types of samples. This review is aimed at providing a general overview of the preparation strategies and methods used in the elemental analysis of food and their applications.